Mobilidade urbana por ônibus em Belo Horizonte: uma proposta de modelo preditivo de viagens e fluxos - Giovanni Candido Miranda (2018)
The fast urbanization process in Brazil has the socio-spatial imbalance as the most characteristic feature. The different accessibility conditions and mobility population follow this characteristic and result in differences in access to opportunities. The increasing use of individual transportation in large Brazilian cities causes economic, social and environmental consequences which directly affects public transportation users. In Belo Horizonte, capital of the state of Minas Gerais / Brazil, the increase in automobile and motorcycle use between 1992 and 2012 was accompanied by a reduction in the number of public transport passengers. Therefore, understanding the dynamics of the demand for public transportation and to creating trends is necessary for the proposal of public policies which purpose is to get efficiency gains in urban mobility, making it more democratic and fair. The present work proposes predictive models to estimate the number trips of public transportation by bus in Belo Horizonte and its potential flows originating from Regional Venda Nova, located in the same county. For the model construction, were used data from the matrix of trips by buses related to the fields and the homogeneous areas of the county, obtained by Pesquisa Origem e Destino from the years 1992, 2002 and 2012. The predictive model of trips by bus results demonstrate the slowdown in the fall observed by the number of journeys in this mode of transportation, as well as the permanency of the process of deconcentration of the trips from Belo Horizonte downtown, both observed between 1992 and 2012. On the other hand, the model potential flows by bus with start in the Regional Venda Nova shows the concentration of the displacements in the main access routes, like as Dom Pedro I, Vilarinho and Presidente Antônio Carlos avenues. The developed methodology enables a replication to estimate trips to the other counties of the RMBH and flows to the further Belo Horizonte zone. The developed models allowed to identify priority areas with a superior need for interventions related to public transportation and traffic, in the way to contribute to the strategic planning of mobility in the metropolis.